The Relationship Between Cognition and Sensorimotor Behavior in an F1 Driving Simulation: An Explorative Study - Eckardt, Nils; Roden, Ingo; Grube, Dietmar; Schorer, Jörg (Frontiers in Psychology, 2020)
Sensorimotor control simultaneously engages multiple cognitive processes, like decision making, intention, processing and the integration of multisensory signals. The reciprocal relationship of cognition and sensorimotor learning is well documented. However, little is known if the status of cognitive skills relates to immediate sensorimotor performance of performing a novel skill. Thus, we aim to explore whether cognitive skills in general and executive functions in particular, may relate to novel sensorimotor performance and adaptive skills. Therefore, 23 male participants engaged in a novel driving simulation for two days. On the first day they accustomed to the F1-simulation until meeting a pre-set threshold (adaption). On the second day, they aimed to drive as fast as possible (performance). In addition, we measure executive functions and global cognition. We found meaningful relationships between response inhibition (Stroop-Colour-Word Test), the driving performance (r = .48, p = .013) and the adaptive ability (r = .34, p = .012). All other tests of executive functioning and global cognition remained non-significant. Our results illustrate an association of driving performance and adaptive abilities and the executive function selective attention/inhibition in a novel F1-simulation. Given the novelty of the task, the ability to adjust sensorimotor behaviour to keep the car on the track seems to be the primary necessary skill to navigate the lap and achieve fast times.